Analysis of the Influence of Work Discipline and Internal Communication on Teamwork at Ilir Timur 1 Police Station, Palembang City - Wiranto, Muhammad Dimas Putra; Afriyani, Fauziah; Kurniawan, Mohammad (Universitas Pamulang, 2025)
This study aims to analyze the influence of work discipline and internal communication on teamwork at Polsek Ilir Timur 1 in Palembang. Teamwork is a crucial element in enhancing operational effectiveness, especially within law enforcement institutions. The research employs a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 75 members of the police sector and analyzed using multiple linear regression with the assistance of SPSS version 26. The results show that both work discipline and internal communication have a significant partial and simultaneous effect on teamwork. These findings indicate that a high level of discipline and effective internal communication can improve coordination, trust, and overall team productivity. The practical implications suggest that the management of Polsek Ilir Timur 1 should regularly implement work discipline training and enhance internal communication through routine meetings or open feedback systems. Further recommendations include promoting two-way communication channels and establishing ongoing discipline evaluations to foster a more conducive and professional work environment.